Effects of Defoliation on Plant Growth of Buffel Grass (Cenchrus ciliaris L.) - Butt, Nasir M; Donart, Garry B; Southward, Morris G; Pieper, Rex D; Mohammad, Noor (Annals of Arid Zone, 2016)
The response of plant growth of buffel grass to cutting was studied during 1986 and 1987 at National Agricultural Research Centre, Islamabad. Sixteen possible combinations of four intervals of cutting; 3, 6, and 9 week and the control and four cutting heights; 10,20, and 30cm stubble heights and the control were applied in randomized complete block design with 4x4 Factorial arrangement. Data on morphological characteristics of plant growth were recorded at prescribed intervals. Clipping after 9 week interval produced comparable growth to control treatment. Clipping at 10cm stubble height was found injurious to plant growth.